Changes in Intraocular Pressure following Narcosis With Medetomidine, Midazolam, and Fentanyl in Association With Initial Intraocular Pressure in Mice. (2nd November 2022) - Binter, Maximilian; Lüdtke, Philipp; Langer, Fridolin; Schigiel, Thomas; Framme, Carsten; Heider, Miriam; Tode, Jan
Abstract: Purpose: This article describes the development of decreased intraocular pressure (IOP) under general anesthesia with medetomidine, midazolam, and fentanyl in mice with normal and elevated IOP. Methods: IOP was measured using the iCare Tonolab rebound tonometer. Twelve 3–4 months-old male and female C57BL/6J mice were randomized to a control group with physiological IOP and a high IOP group with experimentally induced ocular hypertension using tarsal injections of dexamethasone-21-acetate. For anesthesia, medetomidine and midazolam were used, subgroups additionally received fentanyl. IOP was measured every 2.5 min for 30 min. Results: Control group differed with 14.89 mmHg (SEM: 0.58) significantly ( p  = 0.0002) from the high IOP group with initial 20.44 mmHg (SEM: 0.75). All groups showed a significant ( p  < 0.05) decrease in IOP under general anesthesia. There was no significant difference in IOP development and decrease between the group additionally receiving fentanyl and the group without fentanyl. The decrease in IOP was highly dependent on the initial value, with the high IOP group showing a greater decrease. After 10 min, no significant difference in IOP could be detected between the high IOP and control group. Conclusions: In mice, general anesthesia with medetomidine and midazolam leads to a declining IOP over time. Adding fentanyl to the anesthesia did not alter these effects. The decline is time-dependent and IOP-dependent